MULTIMEDIA INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR AKIDAH AKHLAK - Yuslinda, Yuslinda (LPPM IAIN Parepare, 2018)
This article was focused on obtaining empirical data about the learning motivation of morality before it being taught by using interactive multimedia and obtain information whether the application of interactive multimedia can increase students 'motivation to learn at the Islamic Boarding Schools Darul' Ulum Ath-Thahiriyah.The research design used was one group pre tes and post tes design experiments, which means that in this experimental study there was only one experimental group. Subjects are subject to two measurements. The first measurement is done to measure the motivation of students to follow the process of learning the akidah akhlak (pre tes). The second measurement is measuring the motivation of students after following the akidah moral learning process (post tes).The results of this study are: (1) Motivation of students to follow the process of learning the akidah akhlak before being given treatment in the form of the application of interactive multimedia belonging to the high category. (2) The motivation of students to follow the moral learning process after being given treatment in the form of increased interactive multimedia application.. It shows that there is a significant relationship between the application of interactive multimedia with the improvement of learning motivation of students, so that the proposed hypothesis is accepted, that the application of interactive multimedia is effective in increasing the learning motivation of students to follow the learning process of morality